Acute Low-Volume High-Intensity Interval Exercise and Continuous Moderate-Intensity Exercise Elicit a Similar Improvement in 24-h Glycemic Control in Overweight and Obese Adults - Parker, Lewan; Shaw, Christopher S.; Banting, Lauren; Levinger, Itamar; Hill, Karen M.; McAinch, Andrew J.; Stepto, Nigel K. (Frontiers in Physiology, 2017)
Background. Acute exercise reduces postprandial oxidative stress and glycemia; however, the effects of exercise intensity are unclear. We investigated the effect of acute low-volume high-intensity interval-exercise (LV-HIIE) and continuous moderate-intensity exercise (CMIE) on glycemic control and oxidative stress in overweight and obese, inactive adults. Methods. Twenty-seven adults were randomly allocated to perform a single session of LV-HIIE (9 females, 5 males; age: 30±1 years; BMI: 29±1 kg∙m-2; mean±SEM) or CMIE (8 females, 5 males; age: 30±2.0; BMI: 30±2.0) 1 hour after consumption of a standard breakfast. Plasma redox status, glucose and insulin were measured. Continuous glucose monitoring (CGM) was conducted during the 24-hour period before (rest day) and after exercise (exercise day). Results. Plasma thiobarbituric acid reactive substances (TBARS; 29.1 ±12.5%; mean percent change ±90% confidence limit), hydrogen peroxide (43.9 ±16.2%), catalase activity (50.0 ±16.4%), and superoxide dismutase activity (20.9 ±6.4%) increased significantly (p<0.05) from baseline to 1 hour after breakfast (prior to exercise). Exercise significantly decreased (p<0.05) postprandial glycaemia (-5.7 ±4.9%), irrespective of exercise protocol. Only CMIE significantly decreased (p<0.05) postprandial TBARS (CMIE: -32.8 ±7.8%; LV-HIIE: 10.5 ±21.6%) and hydrogen peroxide (CMIE: -24.9 ±14.7%; LV-HIIE: 6.8 ±26.3%). Acute exercise provided a similar significant improvement (p<0.05) in 24-hour average glucose levels ( 4.7 ±2.1%), hyperglycemic excursions (-37.4 ±60.0%), peak glucose concentrations ( 7.9 ±3.6%), and the 2-hour postprandial glucose response to dinner ( 9.1 ±3.9%), irrespective of exercise protocol. Conclusion. Despite elevated postprandial oxidative stress compared to CMIE, LV-HIIE is an equally effective exercise mode for improving 24-hour glycemic control in overweight and obese adults.